PENGEMBANGAN BAHAN AJAR BERBASIS INKUIRI TERINTEGRASI NILAI KARAKTER PEDULI LINGKUNGAN PADA MATERI EKOSISTEM - Lepiyanto, Agil; Pratiwi, Dasrieny (Bioedukasi Jurnal Pendidikan Biologi, 2015)
This study aimed to obtained material learning based on inquiry integrated character values environmental care. This study uses a model of research is RnD. The result of this research show that the quality of material learning based on inquiry integrated character values environmental care is value validation of material expert is Â 90%, design experts is 86 875% and science teacher at 94.74%. material learning based on inquiry-based integrated character values environmental care should continue to be revised in order to obtain better results.Kata Kunci: Bahan ajar, inkuiri, peduli lingkungan